Alternatif Desain Kegiatan Laboratorium Materi Kladogram Berbasis ANCORB : (Alternative Design Laboratory Activities of ANCORB-Based Cladogram Material) - Purnamaulida Pratiwi; Bambang Supriatno; Sri Anggraeni (BIODIK, 2021)
Practicum Activity Design is very useful for students when carrying out practicum. The design can stimulate the formation of a concept that has previously been obtained. This study aims to analyze several laboratory activity designs, then conduct trials and reconstruct Practicum Activity Design which refers to the 2013 curriculum. The research method used is descriptive quantitative. The sample used in this study as many as nine Practicum Activity Design cladograms selected using purposive sampling technique. The research instrument used is the analysis section relevance, competence, construction of knowledge and practical analysis that has been in judgment by experts. The results showed that the relevance aspect already refers to KD, namely the preparation of a cladogram based on the principle of classification. But in some other aspects it has drawbacks. These deficiencies include unclear tools and materials, unclear working procedures, difficult data interpretation processes. So that it does not help students construct knowledge of concepts, principles and theories from the facts that have been obtained. Based on these problems, the DKL cladogram needs to be reconstructed from its relevance, competence, knowledge construction and practical analysis. Abstrak. Desain Kegiatan Praktikum sangat bermanfaat untuk peserta didik ketika melaksanakan praktikum. Desain tersebut dapat menstimulasi pembentukan konsep yang sebelumnya telah diperoleh. Penelitian ini bertujuan untuk menganalisis beberapa Desain Kegiatan Laboratorium lalu lemakukan ujucoba serta merekonstruksi desain yang mengacu pada kurikulum 2013. Metode penelitian yang digunakan adalah deskriptif kuantitatif. Sampel yang digunankan pada penelitian ini sebanyak sembilan DKL kladogram yang dipilih menggunakan teknik purposive sampling. Instrumen penelitian yang digunakan adalah rubrik analisis relevansi, kompetensi, konstruksi pengetahuan dan analisis praktikal yang telah di judgment oleh ahli. Hasil penelitian menunjukkan bahwa aspek relevansi sudah mengacu kepada KD yaitu penyusunan suatu kladogram berdasarkan prinsip klasifikasi. Tetapi pada beberapa aspek lain memiliki kekurangan. Kekurangan tersebut seperti alat dan bahan yang tidak jelas, prosedur pengerjaan yang tidak jelas, proses interpretasi data yang sukar dikerjakan. Sehingga belum membantu peserta didik mengkonstruksi pengetauan konsep, prinsip dan teori dari fakta yang telah diperoleh. Berdasarkan permasalahan tersebut, DKL kladogram perlu untuk dilakukan rekonstruksi dari relevansi, kompetensi, konstruksi pengetahuan dan analisis praktikalnya.